Multi‐steps green process for synthesis of six‐membered functional cyclic carbonate from trimethylolpropane by lipase catalyzed methacrylation and carbonation, and thermal cyclization. (1st December 2015) - Sayed, Mahmoud; Gaber, Yasser; Bornadel, Amin; Pyo, Sang‐Hyun
Abstract : A highly functionalized six‐membered cyclic carbonate, methacrylated trimethylolpropane (TMP) cyclic carbonate, which can be used as a potential monomer for bisphenol‐free polycarbonates and isocyanate‐free polyurethanes, was synthesized by two steps transesterifications catalyzed by immobilized Candida antarctica lipase B, Novozym ® 435 (N435) followed by thermal cyclization. TMP was functionalized as 70 to 80% selectivity of mono‐methacrylate with 70% conversion was achieved, and the reaction rate was evaluated using various acyl donors such as methacrylic acid, methacrylate‐methyl ester, ‐ethyl ester, and ‐vinyl ester. As a new observation, the fastest rate obtained was for the transesterfication reaction using methacrylate methyl ester. Byproducts resulted from leaving groups were adsorbed on the molecular sieves (4Å) to minimize the effect of leaving group on the equilibrium. The difference of reaction rate was explained by molecular dynamic simulations on interactions between carbonyl oxygen and amino acid residues (Thr 40 and Glu 157) in the active site of lipase. Our docking studies revealed that as acyl donor, methyl ester was preferred for the initial conformation of the first tetrahederal intermediate with hydrogen bonding interactions. TMP‐monomethacrylate (TMP‐mMA) cyclic carbonate was obtained in 63% yield (74.1% calculated in 85% conversion) from the lipase‐catalyzed carbonation reaction of TMP‐mMA with dimethylcarbonate, and followed by thermal cyclization of the monocarbonate at 90°C. From the multiple reactions demonstrated in gram scale, TMP‐mMA cyclic carbonate was obtained as a green process without using chlorinated solvent and reagent. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 32:83–88, 2016